Desain Dinding Geser pada Gedung Sederhana dengan menggunakan Software ETABS - Simatupang, Ronald (Zenit, 2013)
Indonesia is a country prone to earthquakes, which Indonesia is  also known as the Ring of Fire area. Itensitas with frequent earthquakes in Indonesia will require the design of earthquake-resistant buildings. One component that is able to resist earthquake loads (lateral force) is the shearwall. Shearwall is one of the structural component that design to take lateral force from earthquake. Using shearwall in the building can reduce the coloumn dimension comparing into building without shearwall. Shearwal can be placed around the pit elevator or stairs, which shaped wall network (core), core-shaped structure is very efficient  in withstanding the lateral forces. From the analysis can be conclude that the building is safe from lateral force. Sherwall also safe from shear force form earthquake .Keywords: shearwall, earthquake, story shear